Silicon negative plate, preparation method thereof and lithium ion battery

By using a composite copper foil structure of polymer substrate and metal copper-plated layer in lithium-ion batteries and laser etching to form grooves, the volume expansion problem of silicon-based negative electrode materials is solved, and the volume energy density and performance of the battery are improved.

CN120511268APending Publication Date: 2025-08-19TIANJIN JUYUAN NEW ENERGY TECH CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510848577.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-24
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

In the prior art, silicon-based anode material has limited battery performance and volume energy density due to volume expansion problems in lithium-ion batteries, and existing laser etching technology affects the battery structure and energy density.

Method used

A composite copper foil structure with a polymer substrate and a metal copper-plated layer is used as the base layer to reduce the thickness of the base layer and form grooves on the active material layer. A micron-scale pore structure is formed by laser etching to absorb the volume expansion of silicon particles.

Benefits of technology

It effectively improves the volume energy density and battery performance of lithium-ion batteries, while improving the safety and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120511268A_ABST
    Figure CN120511268A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to a silicon negative electrode plate, a preparation method thereof and a lithium ion battery. Comprising a substrate layer and an active substance layer coated on at least one side of the substrate layer; the substrate layer comprises a polymer layer and a copper plating layer arranged on the surface of the polymer layer; the active substance layer is provided with a groove, and the active substance layer is made of a silicon-containing material. The composite copper foil structure of the polymer base material and the metal copper plating layer is adopted to reduce the thickness of the substrate layer and increase the relative thickness of the active substance layer, and then the grooves are formed in the active substance layer through laser etching to form the micron-sized pore structure capable of absorbing volume expansion of silicon particles in the charge and discharge process, so that the charge and discharge efficiency is improved. And the volume energy density of the battery is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a silicon negative electrode sheet and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] Silicon-based anode materials are the most promising innovation direction in the field of lithium-ion batteries. The theoretical specific capacity of single-element silicon is as high as 4200mAh / g, which is more than 10 times that of graphite anode. Its volumetric specific capacity can reach 2200mAh / cm 3 , is a graphite negative electrode (760mAh / cm 3 ) is 2.9 times larger than that of the silicon anode. However, the volume expansion problem it faces has become a technical bottleneck restricting its industrial application. Chinese invention patent publication number CN118335902A discloses a silicon-containing negative electrode plate and its preparation method, battery, and electrical equipment. The silicon negative electrode plate includes: a polymer material and a copper seed layer, forming a composite copper foil as a base layer, and a multilayer structure design of a silicon thin film layer and a carbon thin film layer is provided. Among them, although the silicon thin film layer obtained by the process parameters of this case reduces the particle size of the silicon particles, thereby reducing the expansion of the silicon negative electrode, the thickness of the base layer in this case is 3μm to 12μm. The thicker polymer base layer will affect the conductivity, mechanical properties, thermal management performance and bonding strength of the copper foil with the metal coating.

[0003] One of the current mainstream methods to solve the problem of silicon negative electrode expansion is to perform laser etching on the electrode. For example, Chinese patent publication number CN118588901A discloses a negative electrode sheet, its preparation method, and a lithium-ion battery. The negative electrode sheet includes a current collector and an active coating. A double-layer coating method is adopted and a laser etching method is used to form grooves on the active coating. This can inhibit the expansion of the silicon negative electrode and improve the bonding force between the active coating and the current collector by adjusting the proportion of the binder in the double-layer coating. However, the current collector in this case is a copper foil with a thickness of 4μm to 15μm. In order to increase the volume energy density of the battery, the relative thickness of the active coating must be reduced. Although the laser etching modification technology can construct a micro-nano structure on the surface of the silicon material to buffer the volume expansion, it will also destroy the silicon crystal structure. The porous structure formed by etching directly affects the volume energy density of the battery. Summary of the Invention

[0004] In view of this, the present application provides a silicon negative electrode sheet, a preparation method thereof, and a lithium-ion battery, which adopts a composite copper foil structure of a polymer substrate and a metal copper-plated layer to reduce the thickness of the base layer and increase the relative thickness of the active material layer, so as to ultimately achieve the purpose of improving the volume energy density, thereby overcoming the defects of the existing technology.

[0005] To achieve the above object, the detailed technical solution of the present invention is as follows:

[0006] A silicon negative electrode sheet comprises a base layer and an active material layer coated on at least one side of the base layer; the base layer comprises a polymer layer and a copper-plated layer arranged on the surface of the polymer layer; a groove is provided on the active material layer, and the active material layer is a silicon-containing material.

[0007] The thickness of the base layer is 1 μm to 3.5 μm, preferably, the thickness of the base layer is 3 μm;

[0008] The polymer layer is a polyimide PI layer, and the thickness of the polymer layer is 0.5 μm to 1.5 μm. Preferably, the thickness of the polymer layer is 1 μm;

[0009] The copper plating layer has a thickness of 0.5 μm to 1 μm, preferably, the copper plating layer has a thickness of 1 μm;

[0010] The thickness of the active material layer is 40 μm to 50 μm. Preferably, the thickness of the active material layer is 45 μm.

[0011] Preferably, the grooves are obtained by laser etching, and the grooves are arranged at intervals. Preferably, the groove interval distance C is 1-2 mm, preferably 2 mm.

[0012] Preferably, the etching depth B of the groove is 4 μm to 25 μm. Preferably, the etching depth B is 12 μm, and the etching width A is 80 μm.

[0013] When the active material layer is disposed on both sides of the base layer, the grooves on the upper and lower sides of the base layer are staggered. Preferably, the staggered distance D of the grooves is 1 / 2 of the spacing distance C.

[0014] Preferably, the active material layer includes graphite, silicon, a conductive agent and a binder, wherein the mass ratio of the graphite: silicon: conductive agent: binder is (80-97): (1-20): (0.1-5): (2-10), preferably, the mass ratio of the graphite: silicon: conductive agent: binder is 86.55:10:0.25:3.2.

[0015] The conductive agent is carbon black and carbon nanotubes, and the mass ratio of the carbon black to the carbon nanotubes is 4:1.

[0016] The binder is a mixture of polyacrylic acid PAA, carboxymethyl cellulose CMC and styrene butadiene rubber SBR, and the mass ratio of polyacrylic acid PAA:carboxymethyl cellulose CMC:styrene butadiene rubber SBR is 1:1:2.

[0017] A method for preparing a silicon negative electrode sheet, characterized by comprising the following steps:

[0018] S1, using a plasma cleaning machine to clean the polymer layer;

[0019] S2, using a magnetron sputtering device to magnetron sputter deposit a copper layer on the surface of the polymer layer to a preset thickness to obtain a base layer;

[0020] S3, preparing the active material layer, mixing graphite, silicon, conductive agent, and binder according to the mass ratio, and homogenizing the slurry until the slurry is uniform and free of agglomerates;

[0021] S4, uniformly coating the slurry on the surface of the substrate to obtain an active material layer, and compacting the electrode through a rolling process;

[0022] S5, forming grooves on the surface of the active material layer using a laser etching method.

[0023] A lithium-ion battery comprises the negative electrode sheet described above.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The technical solution of the present application forms a PI / Cu composite copper foil as a base layer through a composite structure of a polymer substrate and a metal coating, with the aim of reducing the thickness of the base layer. At the same time, an active material layer is coated on at least one side of the base layer. Preferably, the active material layer is coated on both sides of the base layer. As the thickness of the base layer decreases, the relative thickness of the active material layer increases. Laser etching is then used to form grooves in the active material layer, forming a micron-sized pore structure that can absorb the volume expansion of silicon particles during the charge and discharge process. Thus, the volume energy density of the battery is effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 Schematic diagram of the electrode structure with single-sided coating of PI / Cu substrate layer + laser-etched active material layer;

[0027] Figure 2 Schematic diagram of the pole piece structure with double-sided coating of PI / Cu substrate layer + laser-etched active material layer;

[0028] Figure 3 Schematic diagram of the electrode structure with double-sided coating of PI / Cu substrate layer;

[0029] Figure 4 Schematic diagram of the electrode with double-sided coating of copper foil + laser-etched active material layer;

[0030] Figure 5 for Figure 2 Schematic diagram of the structure of the pole piece size marking. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings and the best embodiments.

[0032] Figure 1 A silicon negative electrode sheet is shown, comprising a base layer and an active material layer coated on one side thereof; the base layer comprises a polymer layer and a copper-plated layer disposed on the surface of the polymer layer; the active material layer is provided with grooves, which are formed by laser etching. The grooves have an etching depth B of 12 μm, an etching width A of 80 μm, and a groove spacing C of 2 mm.

[0033] Figure 2 A silicon negative electrode sheet is shown, comprising a base layer and an active material layer coated on both sides thereof; the base comprises a polymer layer and a copper-plated layer arranged on the surface of the polymer layer; a groove is provided on the active material layer; the groove is obtained by laser etching, and the groove is staggered. Preferably, the groove stagger distance D is 1 / 2 of the spacing distance C.

[0034] Figure 3 This is the control group 1 of this case, which differs from the experimental group in that the active material layers on both sides of the substrate layer are not etched by laser.

[0035] Figure 4 This is shown as the control group 2 of this case, which differs from the experimental group in that the base layer is copper foil.

[0036] Figure 5 The figure shows the schematic diagram of the electrode size marking structure involved in this case, where: A: etching width, B: etching depth, C: spacing distance, D: offset distance.

[0037] The following specific examples illustrate the implementation scheme of this patent.

[0038] Experimental Group 1

[0039] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0040] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 1 μm;

[0041] S2, using a magnetron sputtering device to deposit a copper layer on the surface of the PI layer by magnetron sputtering, so that the copper plating on both sides reaches a preset thickness of 1 μm, and the total thickness of the base layer is 3 μm;

[0042] S3, preparing the active material layer, mixing graphite, silicon carbon or silicon oxide, a conductive agent (carbon black + carbon nanotubes mass ratio of 4:1), and a binder (PAA + CMC + SBR mass ratio of 1:1:2) in a mass ratio of 86.55:10:0.25:3.2, and homogenizing until the slurry is uniform and free of agglomerates;

[0043] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process;

[0044] S5, using a laser etching method on the upper surface of the active coating to form grooves with a spacing of 2 mm, an etching depth of 12 μm, and an etching width of 80 μm.

[0045] Experimental Group 2

[0046] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0047] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 1 μm;

[0048] S2, using magnetron sputtering equipment to deposit a copper layer on the surface of the PI layer, so that the copper plating on both sides reaches a preset thickness of 1 μm; at this time, the total thickness of the base layer is 3 μm;

[0049] S3, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0050] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process;

[0051] S5, forming grooves with a spacing of 1 mm on the upper surface of the active coating using a laser etching method.

[0052] Experimental Group 3

[0053] A method for preparing a negative electrode sheet comprises the following steps:

[0054] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 1 μm;

[0055] S2, using magnetron sputtering equipment to deposit a copper layer on the surface of the PI layer, so that the copper plating on both sides reaches a preset thickness of 1 μm; at this time, the total thickness of the base layer is 3 μm;

[0056] S3, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0057] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process;

[0058] S5, forming grooves with a spacing of 3 mm on the upper surface of the active coating using a laser etching method.

[0059] Experimental Group 4

[0060] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0061] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 0.5 μm;

[0062] S2, using magnetron sputtering equipment to deposit a copper layer on the surface of the PI layer by magnetron sputtering, so that the copper plating on both sides reaches a preset thickness of 0.5 μm; at this time, the total thickness of the base layer is 1.5 μm;

[0063] S3, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0064] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process;

[0065] S5, using a laser etching method on the upper surface of the active coating to form grooves with an interval of 2 mm.

[0066] Experimental Group 5

[0067] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0068] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 1 μm;

[0069] S2, using magnetron sputtering equipment to deposit a copper layer on the surface of the PI layer, so that the copper plating on both sides reaches a preset thickness of 0.5 μm; at this time, the total thickness of the base layer is 2 μm;

[0070] S3, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0071] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process;

[0072] S5, using a laser etching method on the upper surface of the active coating to form grooves with an interval of 2 mm.

[0073] Experimental Group 6

[0074] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0075] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 1.5 μm;

[0076] S2, using magnetron sputtering equipment to deposit a copper layer on the surface of the PI layer by magnetron sputtering, so that the copper plating on both sides reaches a preset thickness of 1 μm; at this time, the total thickness of the base layer is 3.5 μm;

[0077] S3, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0078] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process;

[0079] S5, using a laser etching method on the upper surface of the active coating to form grooves with an interval of 2 mm.

[0080] Control group 1

[0081] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0082] S1, using a plasma cleaning machine to clean the PI layer with a thickness of 1 μm;

[0083] S2, using magnetron sputtering equipment to deposit a copper layer on the surface of the PI layer, so that the copper plating on both sides reaches a preset thickness of 1 μm; at this time, the total thickness of the base layer is 3 μm;

[0084] S3, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0085] S4, evenly coating the slurry on the surface of the PI / Cu composite copper foil, and compacting the electrode through a rolling process.

[0086] Control group 2

[0087] A method for preparing a silicon negative electrode sheet comprises the following steps:

[0088] S1, using a plasma cleaning machine to clean a copper foil with a thickness of 6 μm;

[0089] S2, preparation of active material layer, the ratio is the same as that of experimental group 1;

[0090] S3, evenly coating the slurry on the surface of the copper foil and compacting the electrode through a rolling process;

[0091] S4, using a laser etching method to form grooves with a spacing of 2 mm on the upper surface of the active coating.

[0092] To demonstrate the advantages of this patented solution, thickness expansion rate and volume energy density are compared:

[0093] 1. Thickness Expansion: The thickness of the silicon anode expands after charge and discharge cycles, measured by the thickness expansion rate. The lower the thickness expansion rate, the better the battery performance. At 45°C, the thickness expansion rate was measured after 400 cycles of 1C charge to a maximum voltage of 4.53V, 0.05C charge cutoff, 10 minutes of rest, and 0.5C discharge to 3V. See Table 1 below for the thickness expansion rate.

[0094] Table 1

[0095] 50 times 100 times 200 times 300 times 400 times Experimental Group 1 5.12% 6.11% 7.42% 8.75% 9.89% Experimental Group 2 5.10% 6.0% 7.35% 8.70% 9.80% Experimental Group 3 5.25% 6.4% 7.7% 8.8% 10.2% Experimental Group 6 5.13% 6.06% 7.40% 8.72% 9.82% Control group 1 5.82% 7.0% 8.5% 10.0% 11.6% Control group 2 5.35% 6.5% 7.8% 8.9% 10.5%

[0096] As can be seen from Table 1: Experimental Group 1, Experimental Group 2 and Experimental Group 6, the silicon negative electrode sheet has better battery performance after charge and discharge cycles. In Experimental Group 3, the spacing between the grooves is 3mm, which exceeds the preferred range. The thickness expansion rate is too large during the charge and discharge cycle, and the battery performance also decreases. In Control Group 1, since the grooves are not formed by laser etching, the silicon negative electrode expands rapidly, thus showing a large thickness expansion rate. In Control Group 2, since the base layer uses copper foil, the silicon negative electrode will undergo significant volume expansion during the charge and discharge process. Although the grooves are formed by laser etching, which can suppress the expansion of the silicon negative electrode, the overall battery cycle stability and capacity retention rate are still not as good as those in Experimental Group 1, Experimental Group 2 and Experimental Group 6. Due to the poor safety of Experimental Group 4 and Experimental Group 5, no cycle test was carried out.

[0097] 2. Volumetric Energy Density: A battery's volumetric energy density is an important indicator of its ability to store energy per unit volume, typically expressed in watt-hours per liter (Wh / L). The volumetric energy density of the experimental and control groups was compared using the controlled variable method. While maintaining all other parameters constant, the experimental group's energy density was used as a benchmark for comparison with the other groups, and the average value of five experiments was taken.

[0098] 3. Needle Penetration Test: The battery electrode needle penetration test is a test method used to evaluate the safety performance of lithium-ion batteries and other types of batteries. It primarily simulates the risk of thermal runaway caused by a short circuit due to mechanical damage (such as foreign object penetration) within the battery. Due to the greater dynamic flexibility of PI material, the needle penetration test pass rate is higher, and safety is improved. The needle penetration test speed is 50mm / sec, and only one puncture is performed at each location.

[0099] As shown in Table 2:

[0100] Table 2

[0101]

[0102]

[0103] Table 2 shows that, compared to Experimental Groups 4 and 5, Experimental Groups 1, 2, 3, and 6 all have a PI layer on the silicon anode substrate. However, the thickness of the silicon anode substrate in Experimental Groups 1, 2, and 3 (3μm), and in Experimental Group 6 (3.5μm), is greater than the 1.5μm and 2μm thicknesses in Experimental Group 4 and Experimental Group 5, respectively. Consequently, the needle penetration test pass rate is higher. Control Groups 1 and 2 also demonstrate that using a PI / Cu composite copper foil as the silicon anode substrate improves performance in the needle penetration test. Furthermore, Experimental Groups 1-6 exhibit superior full-charge expansion rate and volumetric energy density compared to Control Groups 1 and 2. In particular, Experimental Groups 4 and 5 achieve higher calculated volumetric energy densities due to the thinner silicon anode substrate, resulting in thinner cells. However, the thinner substrate reduces the needle penetration test pass rate, thus impacting battery safety. Control group 2 also shows from another perspective that if copper foil is used as the base layer, the base layer thickness must be increased. However, the increase in thickness seriously affects the volumetric energy density of the battery and also reduces the battery safety performance. Therefore, the above factors must be comprehensively considered when manufacturing battery cells.

[0104] In summary, experimental group 1 achieved the best results. Specifically, the negative electrode sheet used a PI / Cu composite copper foil with a base layer thickness of 3 μm, an active material layer with a thickness of 45 μm, and laser etching was used to form grooves on the surface of the active material layer. The groove spacing was 2 mm, the etching depth was 12 μm, and the etching width was 80 μm.

[0105] It should be pointed out in particular that the above embodiments are merely preferred implementations of the present invention, and any simple modifications, amendments and substitutions made to the above embodiments based on the technical essence of the present invention fall within the scope of the technical solution of the present invention.

Claims

1. A silicon negative electrode sheet, characterized in that: It includes a base layer and an active material layer coated on at least one side of the base layer; the base layer includes a polymer layer and a copper plating layer arranged on the surface of the polymer layer; a groove is provided on the active material layer, and the active material layer is a silicon-containing material.

2. The silicon negative electrode sheet according to claim 1, characterized in that: The thickness of the base layer is 1 μm to 3.5 μm, preferably, the thickness of the base layer is 3 μm; The polymer layer is a polyimide PI layer, and the thickness of the polymer layer is 0.5 μm to 1.5 μm. Preferably, the thickness of the polymer layer is 1 μm; The copper plating layer has a thickness of 0.5 μm to 1 μm, preferably, the copper plating layer has a thickness of 1 μm; The thickness of the active material layer is 40 μm to 50 μm. Preferably, the thickness of the active material layer is 45 μm.

3. The silicon negative electrode sheet according to claim 1, characterized in that: The grooves are obtained by laser etching.

4. The silicon negative electrode sheet according to claim 3, characterized in that: The grooves are arranged at intervals, and preferably, the groove interval distance C is 1-2 mm, preferably 2 mm.

5. The silicon negative electrode sheet according to claim 4, characterized in that: The etching depth B of the groove is 4 μm to 25 μm. Preferably, the etching depth B is 12 μm, and the etching width A is 80 μm.

6. The silicon negative electrode sheet according to claim 1, characterized in that: When the active material layer is arranged on both sides of the base layer, the grooves on the upper and lower sides of the base layer are staggered. Preferably, the staggered distance D of the grooves is 1 / 2 of the spacing distance C.

7. The silicon negative electrode sheet according to claim 1, characterized in that: The active material layer includes graphite, silicon, a conductive agent and a binder, wherein the mass ratio of the graphite:silicon:conductive agent:binder is (80-97):(1-20):(0.1-5):(2-10), preferably, the mass ratio of the graphite:silicon:conductive agent:binder is 86.55:10:0.25:3.

2.

8. The silicon negative electrode sheet according to claim 7, characterized in that: The conductive agent is carbon black and carbon nanotubes, and the mass ratio of the carbon black to the carbon nanotubes is 4:

1. The binder is a mixture of polyacrylic acid PAA, carboxymethyl cellulose CMC and styrene butadiene rubber SBR, and the mass ratio of the polyacrylic acid PAA:carboxymethyl cellulose CMC:styrene butadiene rubber SBR is 1:1:

2.

9. A method for preparing a silicon negative electrode sheet according to any one of claims 1 to 8, characterized in that: The steps include: S1, using a plasma cleaning machine to clean the polymer layer; S2, using a magnetron sputtering device to magnetron sputter deposit a copper layer on the surface of the polymer layer to a preset thickness to obtain a base layer; S3, preparing the active material layer, mixing graphite, silicon, conductive agent, and binder according to the mass ratio, and homogenizing the slurry until it is uniform and free of agglomerates; S4, uniformly coating the slurry on the surface of the substrate to obtain an active material layer, and compacting the electrode through a rolling process; S5, forming grooves on the surface of the active material layer using a laser etching method.

10. A lithium ion battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Silicon-containing negative pole piece and preparation method thereof, battery and electric equipment

    CN118335902A

  • Negative plate, preparation method thereof and lithium ion battery

    CN118588901A